A computational study on multiple perforated hollow circular section - Woo, Yian Peen (2017)
Originated from the insufficiency in the studies on effect of multiple perforations, and lack of variability in multiple perforation parameters in the available past studies, this study studied the feasibility of the idea of multiple perforated circular hollow section mimicking the geometry and pattern of perforations found on the surface of Cholla cactus (a cacti genus found in hot deserts of American Southwest) skeleton. Effect of perforation parameters on the structural behaviour of the section, the mechanism of load transfer affected by the perforations, and the load carrying capacity of multiple perforated hollow section were extensively investigated by means of finite element analysis. Analysis was carried out under compression, flexural and torsional load cases. The perforation parameters investigated are: shapes and orientations, percentage of perforations, aspect ratios, global arrangement patterns, inclination angles of helices formed where perforations are located, and clearances between neighbouring perforations. Models with perforations arranged in array pattern are found to perform better under compression and flexural load cases. Models with helical pattern perform better under torsional load case. Among models with perforations arranged in helical patterns, equilateral triangle pattern produces the best performance under compression and flexural load cases. On the contrary, right isosceles triangle pattern produces the best performance under torsional load case. Elliptical shape perforation with its larger axis parallel to the longitudinal axis of model produces best performance under compression and flexural load cases, while circular shape produces best performance under torsional load case. Therecommended aspect ratios for elliptical shape depend on the perforation arrangement and load case. The upper limit of percentage of perforations for multiple perforated models is recommended as 30%, beyond which the relationship between structural responses and percentage of perforations ceases to be linear. Based on the analysis of principal stress trajectory (PST) lines, it is found that smaller relative inclination of PST lines at regions after perforations shows less severe load flow obstruction. Models showing better performance are associated with those having smaller size of the regions where PST lines are unable to tilt back to original alignment. It is found that models which produce eddies (in PST diagrams) and load flow recirculations (in load flow orientation diagrams) with smoother shape and smaller size are associated to models experiencing less severe load flow obstruction. Findings from this study indicates that the idea of novel and lightweight multiple perforated hollow circular section is structurally feasible and could be explored further for practical usage.